Peiresc's Mediterranean world - Miller, Peter N. 1964- (Harvard Univ. Press, 2015)
"Antiquarian, lawyer, and cat lover Nicolas Fabri de Peiresc (1580-1637), was a 'prince' of the Republic of Letters and the most gifted French intellectual in the generation between Montaigne and Descartes. From Peiresc's study in Aix-en-Provence, his insatiable curiosity poured forth in thousands of letters that traveled the Mediterranean, seeking knowledge of matters mundane and exotic--travel times and insurance premiums, rare manuscripts and objects from the Orient. Mining the remarkable 70,000-page archive of this Provençal humanist and polymath, Peter N. Miller recovers a lost Mediterranean world of the early seventeenth century that was dominated by the sea: the ceaseless activity of merchants, customs officials, and ships' captains at the center of Europe's sprawling maritime networks. Peiresc's Mediterranean World reconstructs the web of connections that linked the bustling port city of Marseille to destinations throughout the Western Mediterranean, North Africa, the Levant, and beyond. As Miller also makes clear, Peiresc's mastery of practical details and his collaboration with local traders and fixers as well as scholars, sheds new light on the structure of knowledge-making in the age of Bacon, Galileo, and Rubens. Miller shows that Peiresc's pursuit of Oriental studies, for example, depended crucially on his abilities as a man of action. Exploring the historian's craft today against the backdrop of Peiresc's diverse research activities, Peiresc's Mediterranean World suggests new possibilities for scholarship on the past, but also for the relationship between the writing of history and its readers"--Provided by publisher
Includes bibliographical references and index
Algiers, June 1932 -- Marseille-Aix -- Marseille and the French Mediterranean -- Peiresc's letters -- Contingency -- Writing to the Levant 1627-1637 -- Peiresc's names, or, On reading the namescape -- The problem of detail -- The postal link -- The last mile (Mule is king) -- Marseille's merchants -- Marseille merchant families -- Financing, disbursing, reimbursing -- Sanson Napollon -- Naturalizing merchants -- North Africans in Marseille -- Northerners in the Mediterranean -- Ships' captains and patrons -- Tasks entrusted to captains -- Port practices : packaging-plague-quarantine -- Setting sail -- Merchant routes -- Mapping the Mediterranean -- Sicily -- People in motion -- Ottoman Empire news -- Time and timings -- Corsairs -- Ransoming -- End points -- Merchants as intellectual partners -- Before Statistik -- Peiresc's mixing in Cairo's consular politics -- Peiresc and travel -- Where Mediterranean meets Orient : Ethiopia, India, Yemen -- At the still point -- Appendices
Keywords: Peiresc, Nicolas Claude Fabri de / 1580-1637 / Archives; Peiresc, Nicolas Claude Fabri de / 1580-1637; Peiresc, Nicolas Claude Fabri de -- 1580-1637; Geschichte 1600-1700; Geschichte 1600-1650; Intellectuals / France / Archives; Humanists / France / Archives; Commerce; Humanists; Intellectual life; Intellectuals; International relations; Geschichte; Internationale Politik; Mediterranean Region / History / 17th century / Sources; Mediterranean Region / History, Naval / 17th century / Sources; Mediterranean Region / Commerce / History / 17th century / Sources; Marseille (France) / Relations / Mediterranean Region / Sources; Mediterranean Region / Relations / France / Marseille / Sources; France / Intellectual life / 17th century / Sources; France; France / Marseille; Mediterranean Region; Frankreich; Mittelmeerraum; Quelle